Buformin increases radiosensitivity in cervical cancer cells via cell-cycle arrest and delayed DNA-damage repair. Issue 14 (October 2018) - Chen, Ling; Zhang, Ting; Liu, Qiuli; Tang, Mei; Yang, Yu'e; Wang, Yuan; Qiu, Haifeng; Yu, Jinjin
Buformin is a commonly used hypoglycemic agent, and numerous studies have shown that buformin has potent antitumor effects in several malignancies. In this study, we aimed to assess the cytotoxic effect of buformin combined with ionizing radiation (IR) on two human cervical cancer cell lines (Hela and Siha). Cytotoxicity was detected by colony formation assays; impacts on the cell cycle and apoptosis were detected by flow cytometric analyses. Changes in histone H2AX (γ-H2 AX) phosphorylation and impacts on the AMPK/S6 pathway were also explored. Our data show that the combination of buformin and IR had a much stronger antiproliferative effect and resulted in more apoptosis than did buformin or IR alone. Combination treatment with a low dose of buformin (10 µM) and IR (4 Gy) caused G2/M-phase cell cycle arrest. Consistent with these findings, Western blotting showed that the combination of buformin and IR activated AMPK and suppressed S6. In addition, delayed disappearance of γ-H2AX was detected by immunofluorescence in cervical cancer cells treated with buformin plus IR. Taken together, the data indicate that the combination of a low concentration of buformin and IR increases the radiosensitivity of cervical cancer cells via cell cycle arrest and inhibition of DNA repair. Based on these results, we strongly support the use of buformin as an effective agent for improving IR treatment efficiency in the context of cervical cancer. Impact statement: Our idea originated in the thought of discovering new effects of old drugs. Although this study is a basic research, it is very close to clinical treatment. Flow cytometry and immunofluorescence were used to verify that buformin increases radiosensitivity. We aimed to address one of the thorniest problems in treatment process. Based on discovering new effects of old drugs, it is feasible to use buformin as an anticancer drug in clinical application. This will provide new ideas for clinical treatment.